Evaluation of evolutionary engineering strategies for the generation of novel wine yeast strains with improved metabolic characteristics - Horsch, Heidi K. (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Viticulture and Oenology. Wine Biotechnology))--Stellenbosch University, 2008.